Optimisation of SC-CO2 Extraction of Curcuma zedoaria by Response Surface Methodology - Subuki, Istikamah; H. Saidin, Saidatul; Nabilah M. Hisan, Nurul (International Journal of Engineering and Technology, 2018)
In this study, Curcuma zedoaria was extracted using supercritical fluid extraction system (SFE) to obtain valuable extract. Optimisation of extraction condition for high yield and curzerene concentration was carried out by employing the Response Surface Methodology (RSM) particularly, Central Composite Design (CCD).Â The objectives of this work are to investigate the effect of temperature (40oC to 60oC) and pressure (100 to 300 bar) on extraction yield and concentration of major chemical constituents and determine the optimum parameter for high oil yield and curzerene concentration using RSM. Chemical constituents of the oil were analysed using gas chromatography (GC) and Gas Chromatography Spectrometry (GCMS) and showed that curzerene as the key chemical constituent in the oil extract. The results demonstrated that the oil yield obtained were ranged from 0.6 w/w% to 1.8 w/w% and curzerene concentration in range of 1.6% to 4.1%. The optimum parameters predicted by RSM for the highest oil yield and curzerene concentration were found to be 138.65 bar and 40oC, which produced the best oil yield and curzerene concentration predicted as 1.7 w/w % and 3.7% respectively. In conclusion, the pressure and temperature significantly influence the oil yield and oil concentration as p â‰¤ 0.05 for both factor.Â